Face Recognition Model Using Back Propagation - Aswini Priyanka, R; Ashwitha, C; Arun Chakravarthi, R; Prakash, R (International Journal of Engineering and Technology, 2018)
In scientific world, Face recognition becomes an important research topic. The face identification systemÂ is anÂ applicationÂ capable of verifyingÂ a human face from a live videos or digital images. One of the best methods is to compare the particularÂ facial attributes of a person with the images and its database. It is widely used inÂ biometricsÂ and security systems. Back in old days, face identification was a challenging concept. Because of the variations in viewpoint and facial expression, the deep learning neural network came into the technology stack itâ€™s been very easy to detect and recognize the faces. The efficiency has increased dramatically. In this paper, ORL database is about the ten images of forty people helps to evaluate our methodology. We use the concept of Back Propagation Neural Network (BPNN) in deep learning model is to recognize the faces and increase the efficiency of the model compared to previously existing face recognition models.Â Â Â